2016
DOI: 10.1080/15548627.2016.1160176
|View full text |Cite
|
Sign up to set email alerts
|

Ferritinophagy drives uropathogenicEscherichia colipersistence in bladder epithelial cells

Abstract: Autophagy is a cellular recycling pathway, which in many cases, protects host cells from infections by degrading pathogens. However, uropathogenic Escherichia coli (UPEC), the predominant cause of urinary tract infections (UTIs), persist within the urinary tract epithelium (urothelium) by forming reservoirs within autophagosomes. Iron is a critical nutrient for both host and pathogen, and regulation of iron availability is a key host defense against pathogens. Iron homeostasis depends on the shuttling of iron-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
82
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(86 citation statements)
references
References 67 publications
(86 reference statements)
3
82
0
1
Order By: Relevance
“…BeWo cells were prepared for TEM analysis as described previously (39). TEM sections were imaged using a JEOL 1200 EX transmission electron microscope (JEOL USA Inc.).…”
Section: Methodsmentioning
confidence: 99%
“…BeWo cells were prepared for TEM analysis as described previously (39). TEM sections were imaged using a JEOL 1200 EX transmission electron microscope (JEOL USA Inc.).…”
Section: Methodsmentioning
confidence: 99%
“…Siderophores enable bacteria to solubilize iron from their environment to promote their cellular proliferation (Ellermann and Arthur, 2016). For example, uropathogenic E. coli (UPEC) bacteria depend on iron for growth and the ferritinophagy pathway was recently demonstrated to contribute to its increased survival (Bauckman and Mysorekar, 2016). It is suggested that epigenetic changes (i.e., methylation of CDKN2A) in the host uroepithelial cells due to UPEC infection may lead to bladder cancer (Tolg et al, 2011).…”
Section: Bacteria Iron and Cancermentioning
confidence: 99%
“…In addition, UPEC had no significant effect on pMac survival at these time‐points (data not shown). We have previously shown that iron alone promotes UPEC growth in minimal media and in bladder epithelial cells ; thus, the UPEC growth restriction observed in macrophages is attributable to macrophage function.…”
Section: Resultsmentioning
confidence: 97%
“…This is especially relevant in vivo, since macrophages may be exposed to different concentrations of iron over the course of an infection [4]. Interestingly, the host epithelial-iron interactions have the opposite effect on bacterial survival, as our previous work has shown that UPEC is able to access iron within bladder epithelial cells via ferritinophagy, thereby promoting UPEC survival and growth within these cells [19]. We suggest that in the bladder mucosa, UPEC survival and growth within the bladder epithelium may be mitigated by the bladder macrophagic anti-microbial iron regulation response, consistent with previous data showing increased bladder macrophage counts up to 48 hpi with UPEC [40].…”
Section: Discussionmentioning
confidence: 99%